International Experience with Private Sector Participation in Power Grids : Philippines Case Study - World Bank Group (World Bank, Washington, DC, 2016)
The objective of this study is to identify options, taking into account the circumstances of the Philippines, and distill lessons learned from the Philippine experience. The World Bank intends to ultimately integrate the herein findings and recommend best practices for private sector participation in TD systems and open access to TD grids in a comprehensive ESMAP report. The Philippine electricity industry has been undergoing restructuring directed and implemented in accordance with the Electric Power Industry Reform Act or EPIRA. Prior to the EPIRA, central management and control of both generation and transmission in the whole country was under the state‐owned National Power Corporation (NPC). Its electricity supply came from its own power plants and from Independent Power Producers (IPPs). It had sole ownership of the transmission grid and was also responsible for central systems planning and systems operations. Electricity was supplied to end‐users by franchised distribution utilities (DUs) which contracted with NPC and/or IPPs for electricity supply and with NPC for transmission of its power supply. There were also end-users not being supplied electricity by the DUs as they were ‘directly connected’ to the transmission grid by sub‐transmission assets.